Employment, earnings and incomes in Scotland - David Phillips; Tom Waters; Tom Wernham (Institute for Fiscal Studies (IFS), 2023)
How have employment, earnings and incomes performed in Scotland compared with the rest of the UK? What drives geographic inequalities within Scotland?
Keywords: 330; Employment and income; Poverty inequality and social mobility; Benefits; Distributional effects; Employment; Geography; Income taxes; Inequality; Living standards; Poverty; Productivity; Working age benefits; Scotland